Reduction of bioavailability and phytotoxicity effect of cadmium in soil by microbial-induced carbonate precipitation using metabolites of ureolytic bacterium Ochrobactrum sp. POC9 - Zakrzewska, Marta; Rzepa, Grzegorz; Musialowski, Marcin; Goszcz, Aleksandra; Stasiuk, Robert; Debiec-Andrzejewska, Klaudia (Frontiers in Plant Science, 2023)
The application of ureolytic bacteria for bioremediation of soil contaminated with heavy metals, including cadmium (Cd), allows for the efficient immobilization of heavy metals by precipitation or coprecipitation with carbonates. Microbially-induced carbonate precipitation process may be useful also in the case of the cultivation of crop plants in various agricultural soils with trace but legally permissible Cd concentrations, which may be still uptaken by plants. This study aimed to investigate the influence of soil supplementation with metabolites containing carbonates (MCC) produced by the ureolytic bacterium Ochrobactrum sp. POC9 on the Cd mobility in the soil as well as on the Cd uptake efficiency and general condition of crop plants (Petroselinum crispum). In the frame of the conducted studies (i) carbonate productivity of the POC9 strain, (ii) the efficiency of Cd immobilization in soil supplemented with MCC, (iii) crystallization of cadmium carbonate in the soil enriched with MCC, (iv) the effect of MCC on the physico-chemical and microbiological properties of soil, and (v) the effect of changes in soil properties on the morphology, growth rate, and Cd-uptake efficiency of crop plants were investigated. The experiments were conducted in soil contaminated with a low concentration of Cd to simulate the natural environmental conditions. Soil supplementation with MCC significantly reduced the bioavailability of Cd in soil with regard to control variants by about 27-65% (depending on the volume of MCC) and reduced the Cd uptake by plants by about 86% and 74% in shoots and roots, respectively. Furthermore, due to the decrease in soil toxicity and improvement of soil nutrition with other metabolites produced during the urea degradation (MCC), some microbiological properties of soil (quantity and activity of soil microorganisms), as well as the general condition of plants, were also significantly improved. Soil supplementation with MCC enabled efficient Cd stabilization and significantly reduced its toxicity for soil microbiota and plants. Thus, MCC produced by POC9 strain may be used not only as an effective Cd immobilizer in soil but also as a microbe and plant stimulators.